2019
DOI: 10.3390/medicina55070366
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Topical Prostaglandin F2α Analogs on Selected Oxidative Stress Parameters in the Tear Film

Abstract: Background and Objectives: Topically administered antiglaucoma medications, especially those containing benzalkonium chloride (BAC), may cause local adverse effects and compromise ocular surface. The aim of the study was to assess the effect of topical prostaglandin F2α analogs (PGAs): preservative-free latanoprost, BAC-preserved latanoprost, preservative-free tafluprost, and BAC-preserved bimatoprost, on selected oxidative stress parameters in the tear film. Materials and Methods: The patients were divided in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 40 publications
4
3
0
Order By: Relevance
“…Moreover, it should be noted that OSI values were higher in the group of patients treated with BAC-preserved CAI than in the group using preservative-free dorzolamide. This observation is consistent with our previous studies, in which we assessed the influence of selected BAC-preserved prostaglandin F2a analogs (PGAs) (latanoprost, bimatoprost), BACpreserved beta-blocker (BB) (timolol), BAC-preserved alpha 2-agonist (brimonidine) and their unpreserved counterparts [46,47]. However, for PGAs, OSI and TOS were elevated in all patient groups treated with PGAs, both BAC-preserved as well as preservative-free formulations [46].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Moreover, it should be noted that OSI values were higher in the group of patients treated with BAC-preserved CAI than in the group using preservative-free dorzolamide. This observation is consistent with our previous studies, in which we assessed the influence of selected BAC-preserved prostaglandin F2a analogs (PGAs) (latanoprost, bimatoprost), BACpreserved beta-blocker (BB) (timolol), BAC-preserved alpha 2-agonist (brimonidine) and their unpreserved counterparts [46,47]. However, for PGAs, OSI and TOS were elevated in all patient groups treated with PGAs, both BAC-preserved as well as preservative-free formulations [46].…”
Section: Discussionsupporting
confidence: 91%
“…This observation is consistent with our previous studies, in which we assessed the influence of selected BAC-preserved prostaglandin F2a analogs (PGAs) (latanoprost, bimatoprost), BACpreserved beta-blocker (BB) (timolol), BAC-preserved alpha 2-agonist (brimonidine) and their unpreserved counterparts [46,47]. However, for PGAs, OSI and TOS were elevated in all patient groups treated with PGAs, both BAC-preserved as well as preservative-free formulations [46]. The presented results prove that BAC contained in the analyzed formulations contributes to the increase of oxidants in the tear film.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It is also important to emphasize that the number of antiglaucoma medications was correlated with the SOD species in the AH and the BAP in the serum. Previous reports have shown that topical antiglaucoma medications, especially benzalkonium chloride-preserved eye drops, increased oxidative stress in tear film [ 57 , 58 ]; therefore, our results might reflect oxidative stress induced by topical antiglaucoma treatment. Since the type of antiglaucoma medications was not considered in this study, our findings should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 69%
“…In our study, the major metabolites generated from AA, prostaglandin E2 (PGE2), and prostaglandin F2a (PGF2a), were found to be significantly elevated in the patients with kidney stones (Figure 3 and Table S3). PGF2a is a lipid peroxidation product that partially reflects the level of oxidative stress in the body, 38 and its effect of kidney stone formation has been reported in CaOx rats. Animal models confirmed that serum PGF2a was significantly increased in rats with kidney stones 39 .…”
Section: Discussionmentioning
confidence: 99%